Evaluation of glutathione level in gingival crevicular fluid in periodontal health, in chronic periodontitis and after nonsurgical periodontal therapy: A clinicobiochemical study - A M Savita; E Sarun; Shivli Arora; Swathi Krishnan (Wolters Kluwer Medknow Publications, 2015)
Context: Periodontitis is predominantly due to exaggerated host response to pathogenic microorganisms and their products which causes an imbalance between the reactive oxygen species-antioxidant in gingival crevicular fluid (GCF). Glutathione is an important redox regulator in GCF and maintenance of stable reduced glutathione (GSH):oxidized glutathione (GSSG) ratio is essential for periodontal health. Aims: The present study was undertaken to evaluate and compare the level of glutathione and redox balance (GSH: GSSG ratio) in GCF of chronic periodontitis patients, periodontally healthy controls and also to evaluate the effect of nonsurgical periodontal therapy on the level of glutathione and redox balance during 3 months postoperative visit. Study Design: Baseline GCF samples were collected from 20 chronic periodontitis patients and 20 periodontally healthy subjects for GSH and GSSG levels estimation. Periodontitis patients were recalled 3 months postnonsurgical periodontal therapy to re-sample GCF. Materials and Methods: GSH and GSSG levels were measured by high-performance liquid chromatography. The values were statistically analyzed by Paired t-test. Results: The mean GSH and GSSG values in GCF were found to be significantly lower in periodontitis patients pre- and 3 months post-nonsurgical periodontal therapy, compared with those in the control group subjects. In addition, the successful nonsurgical therapy even though leading to a significant improvement in the GSH and GSSG levels, does not restore glutathione concentration to the levels seen in healthy subjects. Conclusion: Successful nonsurgical periodontal therapy leads to significant improvement in the redox balance (GSH: GSSG ratio) in chronic periodontitis patients.